2011
DOI: 10.1016/j.jfms.2011.03.009
|View full text |Cite|
|
Sign up to set email alerts
|

Lower Respiratory Tract Infections in Cats

Abstract: The authors have reviewed a substantial body of literature to provide information on many of the reported bacterial, parasitic, fungal and viral pathogens, including some that occur in Asia. Attention has been given to specific therapy for each pathogen, with evidence-based comments when there is a deviation from routine recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 145 publications
(385 reference statements)
2
29
0
Order By: Relevance
“…Mycoplasma spp. were reported as a common cause of pneumonia in cats in 1 study, 7 and this study would suggest that these organisms can be difficult to identify cytologically. Therefore, the criteria used to define pneumonia need to be specifically determined for the cat.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Mycoplasma spp. were reported as a common cause of pneumonia in cats in 1 study, 7 and this study would suggest that these organisms can be difficult to identify cytologically. Therefore, the criteria used to define pneumonia need to be specifically determined for the cat.…”
Section: Discussionmentioning
confidence: 69%
“…In this study, diagnosis of bacterial pneumonia was confirmed by a combination of clinical findings, BAL cytology qualitative microbiology results, and response to antibiotics in 7 cats. Similar criteria have been used to define lower respiratory tract infection in other studies 3,7 . In cats examined here, 4 of 7 had both intracellular bacteria and positive bacterial cultures identified, while the remaining 3 lacked intracellular bacteria but had positive growth on microbial culture.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…A past work carried out in six experimentally infected foxes showed that animals may develop bronchopneumonia with cough and other signs of heavy respiratory infection, till death in some cases (Borovkova, cited in [25]). In pets, this parasite may cause bronchovesicular sounds, respiratory inflammation, sneezing, wheezing, chronic moist or dry cough, (broncho)-pneumonia respiratory failure and heavy parasite burdens may lead to mortality [10, 31]. More studies are also necessary to evaluate the actual role of E. aerophilus in causing undiagnosed respiratory distresses in companion dogs and cats.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial pneumonia is a relatively rare condition in cats and is usually secondary to hematogenous spread, although inhalation and local extension from other processes (ie, pyothorax) have also been described. 21,22 There was no evidence of retroviral immunosuppressive disease or systemic infection in the cat reported here, and the histopathologic findings made inhalation and impaired clearance the most likely cause of bacterial pneumonia in this case. Although there was no evidence of megaesophagus, the cat was having difficulty swallowing during the last month of life, at which point generalized neuromuscular weakness was apparent.…”
Section: Discussionmentioning
confidence: 53%